Anomalous behavior of the quasi-one-dimensional quantum material Na2OsO4 at high pressure. (March 2019) - Sereika, R.; Yamaura, K.; Jia, Y.; Zhang, S.; Jin, C.; Yoon, H.; Jeong, M.Y.; Han, M.J.; Brewe, D.L.; Heald, S.M.; Sinogeikin, S.; Ding, Y.; et al.
Abstract: Na2 OsO4 is an unusual quantum material that, in contrast to the common 5 d 2 oxides with spins = 1, owns a magnetically silent ground state with spin = 0 and a band gap at Fermi level, attributed to a distortion in the OsO6 octahedral sites. In this semiconductor, our low-temperature electrical transport measurements indicate an anomaly at 6.3 K with a power-law behavior inclining through the semiconductor-to-metal transition observed at 23 GPa. Even more peculiarly, we discover that before this transition, the material becomes more insulating instead of merely turning into a metal according to the conventional wisdom. To investigate the underlying mechanisms, we applied experimental and theoretical methods to examine the electronic and crystal structures comprehensively and conclude that the enhanced insulating state at high pressure originates from the enlarged distortion of the OsO6 . It is such a distortion that widens the band gap and decreases the electron occupancy in Os's t 2g orbital through an interplay of the lattice, charge, and orbital in the material, which is responsible for the changes observed in our experiments. Graphical abstract: Image 1 Highlights: The study reveals that distortion in the edge-shared OsO6 octahedral intensifies with pressure, thereby preventing the formation of the S = 1 state. During compression, sample tends to the insulating state up to 11 GPa. The semiconductor-to-metal transition was discovered at 23 GPa. Sample compression showed a variety of electronically related features affected by pressure. Anomalous behavior of the Na2 OsO4 under high pressure was found to originate from the distortion of the octahedral complex.